2018
DOI: 10.1002/minf.201700138
|View full text |Cite
|
Sign up to set email alerts
|

Cheminformatics Analysis of Dynamic WNK‐Inhibitor Interactions

Abstract: The With-No-Lysine (WNK) serine/threonine kinase family constitutes a unique and distinctive branch of the kinome. The four proteins of this family (WNK1/2/3/4) are involved in blood pressure regulation, body fluid, and electrolyte homeostasis. Herein, we modeled and analyzed the binding modes of all publicly-available small orthosteric and allosteric binders (including WNK463 and WNK467) experimentally tested towards any of the WNK family member. To do so, we relied on state-of-the-art cheminformatics approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…To understand these interactions between kinase and the ligand (WNK463), the lowest energy structures obtained from the MD simulations were considered. Kuenemann and Fourches 53 had observed various hydrogen bond and hydrophobic interactions such as between imidazole nitrogen of ligand and backbone Met 304 and with Asp 368 and Leu 369 , as well as multiple hydrophobic interactions such as Val 235 , Ala 248 , Phe 256 , Leu 272 , Leu 299 , Leu 371 , and Phe 356 . We also have observed the similar interactions between imidazole nitrogen and the backbone Met 304 .…”
Section: Resultsmentioning
confidence: 99%
“…To understand these interactions between kinase and the ligand (WNK463), the lowest energy structures obtained from the MD simulations were considered. Kuenemann and Fourches 53 had observed various hydrogen bond and hydrophobic interactions such as between imidazole nitrogen of ligand and backbone Met 304 and with Asp 368 and Leu 369 , as well as multiple hydrophobic interactions such as Val 235 , Ala 248 , Phe 256 , Leu 272 , Leu 299 , Leu 371 , and Phe 356 . We also have observed the similar interactions between imidazole nitrogen and the backbone Met 304 .…”
Section: Resultsmentioning
confidence: 99%
“…Cells showed viability 98% were incubated with different concentration of primary hits to the 96 well plate for 24 h followed by 4 h incubation with MTT 5 mg/ml. The absorbance was recorded at 580 nm using Synergy/HTX MultiScan reader (BioTek) [23]. Experiments were carried out in triplicate and the Lethal dose (LD 50 ) of each primary hits was calculated and the safety index (SI) was calculated.…”
Section: Resultsmentioning
confidence: 99%
“…For orthosteric WNK inhibitors, this appears to be a limiting factor that cannot be overcome, since the ATP binding site of WNK kinases is highly conserved [69]. However, recent chemoinformatic analysis has revealed that structural specificities among the WNK isoforms do exist, particularly in the allosteric binding sites [78]. The exploitation of these structural differences may be an effective strategy for the development of specific WNK kinase inhibitors and certainly merits further investigation.…”
Section: Orthosteric Wnk Kinase Inhibitorsmentioning
confidence: 99%